GUARANTEE OF HUMAN RIGHTS IN THE CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN - Axmedova Muqaddasxon; Najmutdinova Mehrangiz (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract. The international community has strengthened the main democratic principles and requirements in the field of ensuring human rights and freedoms, and the Universal Declaration of Human Rights, which served as a political and legal basis for the formation of the entire system of international law related to this field, and the Constitution of the Republic of Uzbekistan are devoted to the guarantee of human rights.